Psychological indicators of emotional safety of parents of children with special needs - Ivanashko, Oksana; Virna, Zhanna; Sipko, Lydmila (Psychological Prospects Journal, 2022)
Purpose. The article is devoted to the theoretical and empirical substantiation of psychological indicators of emotional safety of parents of children with special needs. The aim of represented material is theoretical and empirical substantiation of the differences between emotional states of parents of children with special educational needs and parents of children with typical development; outlining the scope of need to introduce psycho-correctional measures for emotional safety of parents of children with special needs.Methods. The article is based on theoretical, empirical and statistical data processing methods. Theoretical (analysis, synthesis, comparison, abstraction, generalization, systematization of scientific literature); empirical (method "Aggressive behavior" (E. Ilyin and P. Kovalev), method "Diagnosis of attitude to the disease of the child" (DSHD)) (V. Kagan and I. Zhuravlyova), method "Self-assessment of emotional state" (A. Wesman and D Rix), the method of "Zung Depression Scale" (adaptation of R. Balashova), statistical data processing: the method of determining the average value, Student's t-test. Statistical data processing was carried out using computer software Statistika 10.Results. Theoretical substantiation of the problem concerns the need for studying the emotional safety of parents of children with special needs due to the obligatory support of correctional work with children with adequate manifestations of emotional states of adults. The developed program of empirical research, as well as the set of methods used for statistical processing of research results allows to specify theoretical positions in the form of real psychological facts: psychological indicators of emotional safety of parents of children with special needs are indexes of nosognosia, control of activity, general tension and general level of depression.Conclusions. Recommendations for the correction of emotional states of parents of children with special educational needs are proposed, which state that their complex socio-psychological content may change depending on the psychological demand. The conclusions indicate the need for further research to substantiate the specifics of emotional states of parents of children with special needs by the differentiation of children's psychophysical disorders.
Keywords: emotional safety, emotional states, child with special needs, parents.